Natural products of relevance in the management of attention deficit hyperactivity disorder. Issue 1 (27th December 2022) - Custódio, Luísa; Vizetto‐Duarte, Catarina; Cebeci, Fatma; Özçelik, Beraat; Sharopov, Farukh; Gürer, Eda Sönmez; Kumar, Manoj; Iriti, Marcello; Sharifi‐Rad, Javad; Calina, Daniela
Abstract: Attention deficit hyperactivity disorder (ADHD) is among the most common neurodevelopmental disorders characterized by motor hyperactivity, attention deficit, distraction, impulsive behavior, and relationship difficulties. It affects children, and thus over the years, there has been growing attention on the use of natural product formulations and their naturally‐occurring bioactive for overcoming the problem of ADHD. Concerning this issue, this review aims to discuss the ADHD treatment potential of natural products/formulations in vitro, in vivo as well as in clinical trials. To gather the most relevant data regarding bioactive compounds with potential therapeutic effects in the management of ADHD, the following databases were searched: PubMed/MedLine, ScienceDirect, and Google Scholar for articles in English. Various medicinal plants and their isolated biomolecules have been evaluated in vitro, in vivo, and in clinical trials for their ability to treat ADHD. Most of the analyzed research results showed an improvement of ADHD signs and symptoms in in vivo models, but the molecular mechanisms of action of the bioactive compounds are unclear and incompletely elucidated. Further studies are needed to determine the bioactive compound responsible for health‐promoting effects in ADHD. In addition, clinical studies should be performed over longer periods with more participants. Abstract : So far there are no concrete recommendations for their use in the treatment of attention deficit‐hyperactivity disorder. This review aims to provide updated clinical evidence on the use of natural products/formulations and their derived constituents for the treatment of attention deficit hyperactivity disorder.